Environmental history recorded over the last 70 years in Biển Hồ maar sediment, Central Highlands of Vietnam - Hướng, Nguyễn-Văn; Schimmelmann, Jan Philipp; Nguyễn-Thùy, Dương; Ojala, Antti; Unkel, Ingmar; Nguyễn-Đình, Thái; Fukumoto, Yu; Doiron, Kelsey E.; Sauer, Peter E.; Drobniak, Agnieszka; Ánh Nguyễn, Nguyệt Thị; Đỗ-Trọng, Quốc; et al. (Quaternary international, 2022)
Global warming enhances atmospheric moisture loading and will likely affect the East-Asian monsoon system across Vietnam. The absence of a long written climate history from Vietnam creates a reliance on geological archives of past monsoon history and regional paleoenvironmental changes to provide a framework for evaluating current climatic trends. Biển Hồ lake (14°03′ N, 108°00′ E) is a volcanic crater (i.e. maar) in Vietnam's Central Highlands that has been accumulating sediment since the Pleistocene. Field campaigns between 2016 and 2018 recovered an abundance of gravity and piston sediment cores extending to a depth of ~15 m, covering approximately the last 30 ka BP. The paleoenvironmental interpretation of Pleistocene and Holocene sediment requires knowledge of modern lacustrine and sedimentary conditions, as well as the origin and transport pathways of the catchment material. Here, we focus on a high-resolution sedimentological and geochemical reconstruction of the recent environmental history - from 1950 AD to the present - based on sediment cores from Biển Hồ maar, in direct comparison with local and regional weather and historic records. The uppermost sedimentary record reflects a substantial anthropogenic influence such as deforestation, military use, crater breaching, dam and sill construction, and reforestation that strongly modified the maar's morphology and hydrology. A strong increase in sedimentation rate during the 1960-70s in Biển Hồ cores coincided with U.S. military activities and water withdrawal. A breach in the maar's rim and the connection to a new external reservoir in 1983-1984 AD increased Biển Hồ water level. Reforestation around most of Biển Hồ’s rim in the 1990s curbed erosion and sedimentation rate. Nutrient availability in Biển Hồ declined in the past ~10 years after the installation of a concrete sill between Biển Hồ and the reservoir to limit water exchange with the more nutrient-rich reservoir. This paper is a calibration study on modern sediment to provide an empirical basis for the interpretation of Biển Hồ’s deeper Holocene and pre-Holocene sedimentary record.
Gesehen am 03.06.2024